2007
DOI: 10.1021/cc070021q
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Solution-Phase Parallel Synthesis of 2-Quinoxalinol Salen Schiff-Base Ligands

Abstract: A solution-phase parallel method for the synthesis of 2-quinoxalinol salen ligands was designed and optimized. The synthesis begins with commercially available 1,5-difluoro-2, 4-dinitrobenzene (DFDNB) and employs a sequence of five straightforward and high-yielding reaction steps. Simple laboratory techniques with low sensitivity to water or air for solution-phase parallel reactions were coupled with convenient workup and purification procedures to give high-purity and yield a small ligand library of 20 compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…9 Labeling studies with 15 N and NMR to identify the asymmetric 2-quinoxolinol intermediate, and a procedure for the preparation of the asymmetric system have been described in detail elsewhere. 9 Labeling studies with 15 N and NMR to identify the asymmetric 2-quinoxolinol intermediate, and a procedure for the preparation of the asymmetric system have been described in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Labeling studies with 15 N and NMR to identify the asymmetric 2-quinoxolinol intermediate, and a procedure for the preparation of the asymmetric system have been described in detail elsewhere. 9 Labeling studies with 15 N and NMR to identify the asymmetric 2-quinoxolinol intermediate, and a procedure for the preparation of the asymmetric system have been described in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…9 During the synthesis of this library, it was found that on reaction of the diamine with aldehyde derivatives, the singly substituted 2-quinoxalinol imines (ex. Synthetic methods with low sensitivity to water or air in solution-phase parallel reactions were coupled with convenient workup and purification procedures resulting in a small ligand library of 20 compounds (4).…”
Section: Introductionmentioning
confidence: 99%
“…<<<<Scheme 10>>>> (e) Although, the solution-phase parallel synthesis of a series of diamino-2-quinoxalinol derivatives was previously reported [58,59]. However, Wu and Gorden had simplified further and optimized the method for the synthesis of diamino-2-quinoxalinols 34 [60] by replacing the scavenger resins used in the previous investigations with 2 equivalents of DIPEA (diisopropylethyl amine) to remove the produced HF and HCl in first step (Scheme 11). They M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 also successfully applied these diamino-2-quinoxalinols as precursors in solution-phase parallel method for the synthesis of 2-quinoxalinol salen ligands 35 [60].…”
Section: Solution-phase Synthesis Of Quinoxaline Derivatives (A)mentioning
confidence: 99%
“…These Schiff bases are all of great importance in the fields of analytical chemistry, stereochemistry, electrochemistry, spectroscopy, molecular self-assembly, supermolecular chemistry, biochemistry model systems, catalysis, materials, nuclear chemistry, and chemical disciplines. [9][10][11][12] However, primary amines or aldehydes are not present in cellulose; cellulose has to be modified to obtain the Schiff base compounds. One effective method is through the selective oxidation of dialdehyde cellulose (DAC) with the use of a further reaction with amines to produce oxidative Schiff alkali cellulose derivatives.…”
Section: Introductionmentioning
confidence: 99%